Poster on poverty in Malawi, 2019-2020 - International Food Policy Research Institute; Banda, Chimwemwe (International Food Policy Research Institute, 2022)
The incidence of poverty at the district level is represented by the poverty headcount ratio, which shows the proportion of the population with consumption expenditures below the national poverty line (MWK 165,879 per person per year, in April 2019 prices). The size of each district represents the number of poor people. Each district is also shaded according to the size of its poverty gap. This is the additional consumption expenditure that it would take to bring an average poor person up to the poverty line, expressed as a shortfall from the poverty line. The map thus shows the depth of poverty throughout Malawi.